2007
DOI: 10.2478/s11756-007-0146-9
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-histological study on shoot bud regeneration in cotyledon cultures of pepper (Capsicum annuum)

Abstract: Adventitious organogenetic structures were produced in vitro using cotyledon explants excised from 14 day-old pepper seedlings. The best response was observed on MS medium containing 5.7 µM indole-3-acetic acid and 8.8 µM 6-benzylaminopurine. However, when transferred onto elongation medium (MS + 2.8 µM gibberellic acid), these structures frequently developed into leaf-like features rather than into normal shoots. Interestingly, the histological study conducted on the cut end of the cotyledonary petiole reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 26 publications
(21 reference statements)
1
4
0
Order By: Relevance
“…As for the interaction, a higher mean number of shoots /explant was recorded (7.26) in cotyledon at 4.0 mg/l BA combined with 0.5 mg/L IAA followed by (6.96) at 5 mg/L BA combined with 0.5 mg/L IAA without significant differences . leaf explant recorded the highest mean number of shoots per explants (5.4) at 4.0 mg/L BA combined with 0.5 mg/L IAA (Table1).This result was agreed with Mezghani et al, (2007) they found that the maximum shoot bud induction of Capsicum annuum using cotyledons as explant cultured on BA in combination with IAA compared with those of control and other treatments. Auxins are using to increase the activating enzyme that break down starch and has the ability to move the active leading to increased proliferation of organogenesis (Taiz and Zeiger2009).The role of auxin in multiplications has been described by Majda and Robert(2018).…”
Section: Resultssupporting
confidence: 86%
“…As for the interaction, a higher mean number of shoots /explant was recorded (7.26) in cotyledon at 4.0 mg/l BA combined with 0.5 mg/L IAA followed by (6.96) at 5 mg/L BA combined with 0.5 mg/L IAA without significant differences . leaf explant recorded the highest mean number of shoots per explants (5.4) at 4.0 mg/L BA combined with 0.5 mg/L IAA (Table1).This result was agreed with Mezghani et al, (2007) they found that the maximum shoot bud induction of Capsicum annuum using cotyledons as explant cultured on BA in combination with IAA compared with those of control and other treatments. Auxins are using to increase the activating enzyme that break down starch and has the ability to move the active leading to increased proliferation of organogenesis (Taiz and Zeiger2009).The role of auxin in multiplications has been described by Majda and Robert(2018).…”
Section: Resultssupporting
confidence: 86%
“…This response occurred especially in genotype AVA-8. Mezghani et al (2007) interpreted the low number of elongated plants found in their work as a consequence of the induction of teratological protuberances, structures that are frequently associated with fasciated and degenerative meristems. Whereas the leaves of shoots developed from hypocotyls had a good appearance ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A strong influence of culture conditions and genotypes has also been demonstrated (Venkataiah et al, 2003). By using cotyledon explants (Agrawal et al, 1989;Mathew, 2002;Venkataiah et al, 2006) and by applying the most common regeneration protocols for hot pepper (Mathew, 2002;Venkataiah et al, 2001), Mezghani et al (2007) produced shoot buds for a hot pepper genotype (cv. Baklouti).…”
Section: Discussionmentioning
confidence: 99%